APLIKASI WATPASDROID UNTUK PERBAIKAN SAMBUNGAN POROS MESIN LISTRIK PADA PRAKTIKUM UJI PEMBEBANAN MOTOR - Mochammad Darwis (UIN Sunan Kalijaga Yogyakarta, 2016)
The quality of an electrical connection engine shaft which is not straight and not exactly center can damage the engine crankshaft and the rotated engine. The Power used will be enlarged and the temperature of the equipment will increase. Increasing temperatures will shorten the life of the equipment. Previously, to test the quality of the connection shaft, we use a waterpas. Disadvantage of this method is a waterpas, only measures the flatness of the field in one or two areas only. Watpasdroid application developed as a quality improvement solution for shaft connection which is cheaper and easier. With this app, android phones can be used to measure how much the value of the tilt on the axis x, y and z. The value-added applications are high level of accuracy and simplicity. Without the need to add another device, the Android phone quite put on the field to be measured. Watpasdroid already used in Electric Drive laboratory in Electronic Engineering Polytechnic Institute of Surabaya (PENS), to check the connections of the engine shaft on motor loading test. Application developed using Basic4Android program (B4A), which uses the Basic programming language, which is easier than the other developer programs based on Java.